Tramadol for acute pain management in conjunction with serotonin receptor antagonist antiemetic drugs - Lima, Vinícius [UNESP]; El Dib, Regina [UNESP]; Ganem, Eliana [UNESP]; De Barros, Guilherme A.M. [UNESP] (Wiley, 2016)
This is the protocol for a review and there is no abstract. The objectives are as follows: To determine any interaction of serotonin receptor antagonist antiemetic drugs on the analgesic effect of tramadol for acute pain management in adults.